Pyrolysis of marine waste to pyrolytic oil and its application in compression ignition engine: Engine performance, combustion, and emission analysis. Issue 3 (14th September 2022) - Singh, Rohit Kumar; Pannase, Ajinkya Mukund; Joshi, Mahesh Prakash; Ruj, Biswajit; Sadhukhan, Anup Kumar; Gupta, Parthapratim
ABSTRACT: Due to dumping of huge quantity of waste nylon into the sea in the form of fishing nets and ropes, there is a great potential to recover energy from such trash as well as to clean up the marine environment. The high energy content of these waste makes it a prospective source of fuel. This work reports the recovery of pyrolytic pyrolysis oil (PPO) from pyrolysis of waste fishing nets and ropes (nylon) at a temperature of 500°C. Initially, the obtained PPO was characterized using physical properties, GC-MS, and FTIR and further compared with diesel fuel oil properties. The properties of the obtained oil exhibit a high similarity with the conventional diesel fuel. Secondly, the obtained crude PPO was utilized in Combustion ignition engine in blends with diesel as 10, 20, 30 and 50% volume to study the combustion and emission characteristics. Increase in PPO concentration results in the increased in-cylinder pressure, while an increase in PPO concentration has no severe effect on the ignition delay. The brake thermal efficiency (BTE) of the engine was found to improve with the minor addition of PPO to diesel; also the specific fuel consumption (SFC) was observed to reduce for lower PPO blends. The exhaust analysis reports that the emissions such as CO, CO2, NOx, and UHC were observed to increase with an increase in the concentration of PPO in the blends with a small fraction. The combustion and performance results for the blends up to 20% were found to be on par with diesel engine performance.